Pengaruh Pengembangan Karir, Motivasi Dan Kompetensi Terhadap Kinerja Pegawai Dinas Ketahanan Pangan Provinsi Kalimantan Tengah - Julianto, Hendra; Christa, Usup Riassy; Hidayat, Deddy Rakhmad (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2020)
Purpose, - The purpose of this research is to find out and obtain a study of the influence of career development, motivation and competence on the performance of employees of the Department of Food Security of Central Kalimantan Province.Design/methodology/approach - This research is a quantitative descriptive study with a total of 60 respondents. The instrument testing uses validity and reliability tests. While the data analysis method uses multiple linear regression analysis with t test, F test and R2.Findings - The results showed that career development had a significant positive effect on employee performance, motivation had a significant positive effect on employee performance, Competence has a significant positive effect on employee performance, self-development, motivation and competence has a significant positive effect together on employee performance.